2014
DOI: 10.1007/s40273-014-0162-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Current Cost-Effectiveness Thresholds for Low- and Middle-Income Countries Useful? Examples from the World of Vaccines

Abstract: The World Health Organization's CHOosing Interventions that are Cost Effective (WHO-CHOICE) thresholds for averting a disability-adjusted life-year of one to three times per capita income have been widely cited and used as a measure of cost effectiveness in evaluations of vaccination for low-and middle-income countries (LMICs). These thresholds were based upon criteria set out by the WHO Commission on Macroeconomics and Health, which reflected the potential economic returns of interventions. The CHOICE project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 27 publications
1
75
0
6
Order By: Relevance
“…More often than not, the magnitude of this threshold has little or no empirical foundation; in Bulgaria, no mandatory consensus standard exists for it. On the other hand, the often adduced WHO-CHOICE threshold of 1 to 3 times GDP per capita [55], also cited by the National Council of Pricing an Reimbursement [56], has several well-acknowledged shortcomings [57,58] and is therefore contentious. Invoking thresholds that do not reflect the opportunity costs of a particular health care system is not expedient to advance the health-related well-being of the population it serves.…”
Section: Discussionmentioning
confidence: 99%
“…More often than not, the magnitude of this threshold has little or no empirical foundation; in Bulgaria, no mandatory consensus standard exists for it. On the other hand, the often adduced WHO-CHOICE threshold of 1 to 3 times GDP per capita [55], also cited by the National Council of Pricing an Reimbursement [56], has several well-acknowledged shortcomings [57,58] and is therefore contentious. Invoking thresholds that do not reflect the opportunity costs of a particular health care system is not expedient to advance the health-related well-being of the population it serves.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, thresholds in LMICs should be informed by the alternative ways the health resources could be allocated, as well as local budget constraints 41. As a result, it is important to consider the findings of budget impact analyses for the various influenza vaccination strategies under consideration.…”
Section: Estimating and Presenting Results Of The Economic Evaluationmentioning
confidence: 99%
“…19 The authors of most papers (95%) were favorable to the intervention. Since Brazil does not have a locally established cost-effectiveness threshold, we used WHO' CHOICE criteria, 11 as used by others, particularly in low-and middle-income countries, 55,56 to interpret the reviewed studies' results. In all 13 reviewed studies that reported ICERs, the vaccination program was below the threshold of cost-effectiveness (<3 GDP/ DALY).…”
Section: Discussionmentioning
confidence: 99%
“…WHO' CHOICE criteria for cost-effectiveness threshold has been discussed in the literature. 55,56 A criticism is that it "sets such a low bar for cost-effectiveness that very few interventions with evidence of efficacy can be ruled out,"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation